Photochemical reduction of U(VI) in aqueous solution in the presence of 2-propanol - Salomone, Vanesa Natalia (2014)
The efficiency of the photochemical reduction of uranyl (UO22+) (0.25 mM, pH 3) was analyzed in theabsence and in the presence of 2-propanol (2-PrOH), evaluating the effect of anions (nitrate, acetate andperchlorate) and the use of quartz and glass photoreactors. A higher removal was observed under allconditions with the quartz photoreactor; the best system was that starting from uranyl nitrate, where a90% UO22+removal was attained after 15 min irradiation. In the absence of 2-PrOH, the acetate systemwas the only one where some U(VI) removal was observed (15% after 15 min in the quartz photoreactor)but, in the presence of the alcohol, the acetate system was the least reactive. Under irradiation, nitrateand acetate were consumed during the reaction, causing important effects on the uranyl conversion,while perchlorate was inactive. Uranium was removed from the system as a solid residue in the case ofnitrate- (as U(IV)) and perchlorate-containing systems (as U(VI)), while it remained in solution in thecase of the acetate systems. Mechanisms are proposed for the different conditions. The importance ofnitrate as a reducing agent of uranium species has not been previously reported. The use of uranyl nitrateand short-near UV?vis light seems to be the most advisable way of removing uranyl from solutions, inthe form of a stable precipitate.